Design of a Web-Based Student Council President Election Management Application Using the Simple Additive Weighting (SAW) Method - Diaz Syahputra; Muhammad Hendri; Sahara Abdy; David Chandra (Jurnal Informatika Logika, 2026)
The election of the Student Council President is a routine school activity aimed at selecting a student leader democratically. However, manual election processes often encounter challenges such as time constraints, a lack of transparency, and the potential for vote-counting errors. To address these issues, this study designs a web-based Student Council President election management application utilizing the Simple Additive Weighting (SAW) method. The SAW method was selected for its ability to determine the best alternative based on predefined criteria weightings, thereby making the decision-making process more objective. A case study was conducted at SMKN 13 Medan, incorporating criteria such as leadership, communication, creativity, active participation, and personality. The research results indicate that implementing the web-based application enhances efficiency, transparency, and accuracy in the election process. Consequently, the system is expected to assist the school in conducting elections more effectively and in a manner that is modern and aligned with democratic principles.